Microplastic Pollution in Mindanao's Taguibo River Watershed Forest Reserve: Characterization, and Distribution Patterns, and Implications for Freshwater Ecosystem Conservation - Tuquero Banda, Marybeth Hope; Cumba Olayon, Mary Cena; Tapere Inocente, Sherley Ann; Masaya Segovia, Jayson Leigh; Bedoya, Nelieta Arnejo; Bigcas, Evelyn Varquez; Disalongan Lomantong, Abdul-Nasser; Bacsarpa, Charmjill Yap; Candilada Aporbo, Jhon Carlo; Reble, Darlene Magante; Bacosa, Hernando Pactao; Lubguban, Arnold Ano-os; et al. (Applied Science and Engineering Progress, 2024)
Despite increasing awareness of microplastic pollution and the harm it brings to terrestrial ecosystems and human body, few research works have examined how it contributes to freshwater environments, particularly forest reserves. Microplastic presence and characteristics were examined in Mindanao's Taguibo River Watershed Forest Reserve (TRWFR). Three (3) sampling sites along the river stretch were chosen. Analysis of water and sediment samples found microplastic abundances at 477.78 ± 182.83 pa/m3 and 17.04 ± 14.80 pa/kg, respectively. These microplastics varied in size, shape, and color. A total of 9 and 7 color variations were detected from water and sediment samples, respectively. Brown (43.02%) and black (17.44%), and fibers (39.53%) and films (24.42%) were the most common microplastics from water samples. White (30.43%), and blue and brown (21.74%), and filament (69.57%) were the most common microplastics from sediment samples. FTIR-ATR spectroscopy described the microplastics further. A total of 13 polymer types were identified in water samples, while 8 polymer types were identified in sediment samples. Polymer types such as polyacetylene and regenerated cellulose fibers were mostly found in water samples; and polypropylene and regenerated cellulose fibers from sediment samples. This study shows microplastic pollution in the TRWFR. Microplastic incidence and distribution patterns vary among collection locations, suggesting some areas are more susceptible to pollution. This work improves our understanding of freshwater microplastic contamination and underscores the need to monitor and reduce microplastic pollution to preserve the ecological balance in the Taguibo River and its surroundings.